Identification of an Anchor Residue for CheA-CheY Interactions in the Chemotaxis System of Escherichia coli - Thakor, Hemang (American Society for Microbiology, 2011)

(untitled)
Transfer of a phosphoryl group from autophosphorylated CheA (P-CheA) to CheY is an important step in the bacterial chemotaxis signal transduction pathway. This reaction involves CheY (i) binding to the P2 domain of P-CheA and then (ii) acquiring the phosphoryl group from the P1 domain. Crystal structures indicated numerous side chain interactions at the CheY-P2 binding interface. To investigate the individual contributions of the P2 side chains involved in these contacts, we analyzed the effects of eight alanine substitution mutations on CheA-CheY binding interactions. An F214A substitution in P2 caused ∼1,000-fold reduction in CheA-CheY binding affinity, while Ala substitutions at other P2 positions had small effects (E171A, E178A, and I216A) or no detectable effects (H181A, D202A, D207A, and C213A) on binding affinity. These results are discussed in relation to previous in silico predictions of hot-spot and anchor positions at the CheA-CheY interface. We also investigated the consequences of these mutations for chemotaxis signal transduction in living cells. CheA(F214A) was defective in mediating localization of CheY-YFP to the large clusters of signaling proteins that form at the poles of Escherichia coli cells, while the other CheA variants did not differ from wild-type (wt) CheA (CheA(wt)) in this regard. In our set of mutants, only CheA(F214A) exhibited a markedly diminished ability to support chemotaxis in motility agar assays. Surprisingly, however, in FRET assays that monitored receptor-regulated production of phospho-CheY, CheA(F214A) (and each of the other Ala substitution mutants) performed just as well as CheA(wt). Overall, our findings indicate that F214 serves as an anchor residue at the CheA-CheY interface and makes an important contribution to the binding energy in vitro and in vivo; however, loss of this contribution does not have a large negative effect on the overall ability of the signaling pathway to modulate P-CheY levels in response to chemoattractants.